Plant Phenotypic and Transcriptional Changes Induced by Volatiles from the Fungal Root Pathogen Rhizoctonia solani - Cordovez, Viviane; Mommer, Liesje; Moisan, Kay; Lucas-Barbosa, Dani; Pierik, Ronald; Mumm, Roland; Carrion, Victor J.; Raaijmakers, Jos M. (Frontiers in Plant Science, 2017)
Beneficial soil microorganisms can affect plant growth and resistance by the production of volatile organic compounds (VOCs). Yet, little is known on how VOCs from soil-borne plant pathogens affect plant growth and resistance. Here we show that VOCs released from mycelium and sclerotia of the fungal root pathogen Rhizoctonia solani enhance growth and accelerate development of Arabidopsis thaliana. Seedlings briefly exposed to the fungal VOCs showed similar phenotypes, suggesting that enhanced biomass and accelerated development are primed already at early developmental stages. Fungal VOCs did not affect plant resistance to infection by the VOC-producing pathogen itself but reduced aboveground resistance to the herbivore Mamestra brassicae. Transcriptomics of A. thaliana revealed that genes involved in auxin signaling were up-regulated, whereas ethylene and jasmonic acid signaling pathways were down-regulated by fungal VOCs. Mutants disrupted in these pathways showed similar VOC-mediated growth responses as the wild-type A. thaliana, suggesting that other yet unknown pathways play a more prominent role. We postulate that R. solani uses VOCs to predispose plants for infection from a distance by altering root architecture and enhancing root biomass. Alternatively, plants may use enhanced root growth upon fungal VOC perception to sacrifice part of the root biomass and accelerate development and reproduction to survive infection.